Immune mechanisms in fish skin against monogeneans--a model - Buchmann, K (Folia parasitologica, 1999)
Host responses against skin inhabiting monogeneans are commonly observed but the responsible immune mechanisms in the fish skin are sufficiently described. Based on recent knowledge of fish immunity and skin response mechanisms in mammals a model for the skin immunity in fish to monogenean infections is proposed. Important cellular components of the model are the epithelial cells, the mucous cells and leucocytes. The release of cytokines, e.g., IL-1, following mechanical or chemical injury of the epithelial cells, initiates a series of events leading to decrease of the ectoparasite population. Cytokines (e.g., IL-1, TNF, INF) are suggested to affect secretions from mucous cell and attract neutrophils and macrophages. Leukotrienes are probably involved in the inflammatory reactions. The subsequent production of humoral substances (among others complement factors and peptides) could be responsible for the antiparasitic response in the later stages of infection. Although non-specific factors dominate the response, the involvement of specific antibodies and lymphocytes cannot be excluded.
Keywords: Antibodies, Helminth; Animals; Complement System Proteins; Trematoda; epidermis; Epidermis; Cytokines; infekce červy třídy Trematoda; Trematode Infections; cytokiny; nemoci ryb; protilátky helmintové; infestace ektoparazity; Ectoparasitic Infestations; Fish Diseases; Fishes; ryby; leukocyty; Leukocytes; modely imunologické; Oncorhynchus mykiss; zvířata; komplement; Models, Immunological